The genome sequence of a phantom cranefly, Ptychoptera contaminata (Linnaeus, 1758) [version 1; peer review: 1 approved, 2 approved with reservations] - Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from a male specimen of Ptychoptera contaminata (phantom cranefly; Arthropoda; Insecta; Diptera; Ptychopteridae). The genome sequence has a total length of 204.08 megabases. Most of the assembly (83.64%) is scaffolded into 6 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled, with a length of 17.64 kilobases. Gene annotation of this assembly on Ensembl identified 11,102 protein-coding genes.